FEASIBILITY OF A RETAIL CBDC IN UZBEKISTAN: ANALYSIS OF STRUCTURAL BARRIERS AND PROJECTED IMPACT ON MONETARY AGGREGATES (Academicia Globe: Inderscience Research, 2025)
This study analyses the technical and economic feasibility of implementing a Central Bank Digital Currency (CBDC)—the "Digital Som"—in Uzbekistan. Using the STEEP framework, we evaluate infrastructural readiness, contrasting the nation's high digital connectivity (94.2% internet penetration in 2025) against the persistence of a significant shadow economy (~35% of GDP). The core of the paper models the "Substitution Effect," projecting how a Digital Som would alter the composition of the Money Supply. We hypothesize that while high smartphone adoption favours feasibility, the Digital Som will primarily substitute Cash-in-Circulation rather than Commercial Bank Deposits, minimizing the risk of financial disintermediation in the short term. The study concludes that the Digital Som’s primary utility lies in fiscal transparency and reducing the "dollarization" of domestic savings.